MANAJEMEN BAHAN ORGANIK UNTUK REKLAMASI LAHAN: ANALISIS HUBUNGAN ANTARA SIFAT KIMIA TANAH DAN PERTUMBUHAN POHON DI LAHAN TIMBUNAN BEKAS TAMBANG BATUBARA PT BUKIT ASAM (PERSERO), Tbk. - Liesna Amelia; Didik Suprayogo (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Reclamation of ex-mining land is important in restoring environmental conditions approaching the original soil conditions before mining. The aim of this study was is to observe the effect of organic matters and organic matter placement on soil fertility in an effort to improve growth of Merbau (Intsia spp. (L bijuga, L palembanica) and Sengon Buto (Enterolobium cyclocarpum) trees. The study was conducted on a former mining land area of PT. Bukit Asam, South Sumatra. The experimental design used in this study was factorial randomized block design with organic matter factors and organic matter placement. Parameters used for evaluating soil fertility were pH, Al-dd, H-dd, C-organic, total-N, available-P, potential P and K. Parameters of tree growth measured were height, diameter, number of leaves and number of branches and roots. The results showed that organic matter had significant effect on soil fertility and could increase the rate of tree growth and root development. The use of oil palm empty fruit bunch compost significantly increased soil fertility. Results of this study explained the positive relationship between soil fertility with the growth of young trees.